Hoffmann Photograph MS608_3_9_005 - (:unkn) unknown (My University, 2013)
Black and white shot of a pair of Girls fencing on stage at Palladium show.

Handwritten note: "Gertrude Hoffmann Girls | Geo Black's London Palladium Show | England. | Natalie and
Keywords: Gertrude Hoffmann Company